CONSTRUCTION SOLUTIONS ROTATIONAL MOLDING MACHINES POLYMER MATERIALS - Głogowska, Karolina (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The rotational moulding is most commonly used for the manufacture of seamless hollow products, the wall thickness of which may be easily adjusted by changing the ratio of rotational speed of the mould around the main and auxiliary axis. The technology of rotational moulding is used for the manufacture of large-size products of polymeric material, such as water or oil tanks, waste containers, home sewage treatment plants, kayaks, separators, sewerage wells, road barriers and other. This production method allows the manufacture, according to a given mould, of both very simple and highly complex products from thermoplastic polymeric materials. The rotational moulding is a processing process, which uses the centrifugal force influencing the material being moulded, contained in the moulding cavity of the casting mould. During this process, the mould loaded with material is rotating and as a result, the liquid or plasticized material is evenly distributed throughout all walls of the moulding cavity. The presented paper characterizes the process, machines and equipment for rotational moulding of polymeric material, and discusses the advantage and disadvantages of this processing method.